2018
DOI: 10.1029/2018gl077932
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability of Seasonality of Rainfall Over India

Abstract: We analyzed 113 years (1901–2013) of daily rainfall over India to investigate spatiotemporal variability of rainfall seasonality. Rainfall seasonality and mean annual rainfall were found to be high over the Western Ghats, central, and northeastern parts of India and over the Indo‐Gangetic plains, and low over northwest, southern, and northernmost parts of India. Significant decreasing trends in seasonality coupled with decreasing rainfall were found over parts of central India, the Indo‐Gangetic plains, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…during June-September. However, the duration of the southwest monsoon rainfall over Rajasthan is very short due to late arrival and early withdrawal (Sahany et al 2018, Mehfooz et al 2005. Therefore, relative entropy is seen to be high as rainfall is concentrated in a short duration.…”
Section: Relative Entropymentioning
confidence: 99%
See 2 more Smart Citations
“…during June-September. However, the duration of the southwest monsoon rainfall over Rajasthan is very short due to late arrival and early withdrawal (Sahany et al 2018, Mehfooz et al 2005. Therefore, relative entropy is seen to be high as rainfall is concentrated in a short duration.…”
Section: Relative Entropymentioning
confidence: 99%
“…Ayoade (1988) attempted to incorporate the effect of changes in total precipitation accumulation and temporal distribution into a single metric, called rainfall seasonality. Researchers quantify rainfall seasonality in various ways by using different statistical methods (Walsh and Lawler 1981, Wilson and Dawe 2006, Adejuwon 2012, Sperber et al 2013, Feng et al 2013, Pascale et al 2015, Sahany et al 2018. For example, Walsh and Lawler (1981) investigated rainfall seasonality over the African region by linking rainfall seasonality with latitudes and they found that seasonality changes with latitudes; it is low in equatorial regions but increases rapidly with latitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the temporal dynamics of productivity in relation to inter-annual variability of rainfall are more poorly resolved [2,[4][5][6][7]. In particular, how vegetated ecosystems will respond to observed and projected shifts in the mean amount and/or variability of rainfall, as well as the seasonal timing, frequency, and intensity of rainfall events (e.g., [8][9][10][11][12]) remains uncertain. Understanding how temporal patterns of rainfall influence plant productivity and growth is thus crucial for modelling and predicting vegetation responses under present or future climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the second stage of analysis a pixel-wise linear trend analysis is performed on the groundwater anomaly (GW_A) estimates. Further, to evaluate the variability of precipitation over the basin an entropy-based seasonality index is applied to the IMD precipitation over the basin (Feng et al, 2013;Sahany et al, 2018).…”
Section: Methodsmentioning
confidence: 99%